P-64 DOWNSTAGING STRATEGY FOR LIVER TRANSPLANTATION IN HEPATOCELLULAR CARCINOMA. A COHORT STUDY IN A COLOMBIAN HOSPITAL - Juan Ignacio Marin-Zuluaga; Andres Fernando Rodriguez-Gutierrez; María Fernanda Saavedra-Chacón; Christian Ernesto Melgar-Burbano (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Hepatocellular carcinoma (HCC) with low tumor burden can be treated by liver transplantation (LT). Downstaging is a strategy to reduce tumor burden and allow transplantation. Objectives: To present the features and outcomes of patients undergoing LT with a downstaging and to compare them with patients transplanted according to Milan criteria Patients / Materials and Methods: Retrospective cohort study of transplanted patients from July 2012 to January 2024 in a Colombian hospital. Downstaging was carried out in accordance with UNOS criteria. Death and recurrence of HCC were the primary outcomes. Cox proportional hazards model was adjusted for age and Child-Pugh score. Results and Discussion: 79 patients, 17 in downstaging group (DG) and 62 in Milan Group (MG). All patients had cirrhosis. Median age was 60 years and 71% were men. DG has less diabetes mellitus than MG (24% vs. 48%), less comorbidities (82% vs. 92%), better Child-Pugh, less ascites (6% vs. 50%), less encephalopathy (18% vs. 45%) and less variceal bleeding (17% vs. 32%). In DG, the median number of tumors was 2 (IQR: 1-3, 29% with just one) and in MG it was 1 (IQR: 1-1, 79% with just one). Dowstaging was performed using either TACE alone (88%) or in combination with radiofrequency ablation (22%). Liver specimens showed a high sum of tumor diameters in DG (4.8 cm vs. 3.0 cm), however, DG had less microvascular invasion (18% vs. 37%) and a better profile of tumor differentiation. Recurrence was 11.8% in DG and 8.2% in MG (p-value = 0.926, figure). In DG, there was a death rate of 6% while in MG it was 18% (p-value = 0.285). Conclusions: Downstaging appeared to be a successful strategy for LT that could be used to expand the Milan Criteria in Colombia. Less sick patients in DG (necessary for locoregional therapy), could have favored survival.